Analisis pertumbuhan ekonomi terhadap tingkat kesejahteraan di Sumatera Utara: (Economic growth and human well-being) - Sagala, Donar (EcoProfit: Sustainable and Environment Business, 2024)
The aim of this research is to see how economic growth, poverty, and welfare levels in North Sumatra Province, Indonesia, relate to each other. This research investigates how these components interact in regional development using various theoretical frameworks. This research method involves the analysis of secondary data from North Sumatra Province, including data on economic growth, poverty levels, and indicators of people's welfare. Economic data will be evaluated using economic growth theory, and factors such as access to clean water, electricity, schools, health facilities, and infrastructure will be considered in the poverty and welfare analysis. It is hoped that the results of this research will provide in-depth insight into how economic growth impacts community welfare and poverty levels at the provincial level. It is hoped that this research will provide policy benefits for local governments as they create plans for sustainable economic development, improve community welfare, and overcome poverty.